Constraint preconditioning for indefinite linear systems - Keller, C; Gould, N; Wathen, A (Unspecified, 1999)
The problem of finding good preconditioners for the numerical solution of indefinite linear systems is considered. Special emphasis is put on preconditioners that have a 2 x 2 block structure and which incorporate the (1, 2) and (2, 1) blocks of the original matrix. Results concerning the spectrum and form of the eigenvectors of the preconditioned matrix and its minimum polynomial are given. The consequences of these results are considered for a variety of Krylov subspace methods. Numerical experiments validate these conclusions.